Платить надо, брат!: [повести] / Евгений Монах - Монах Евгений Михайлович (Воровской роман, 2003)
Экземпляры: ф.7 (2004) / Инвентарный номер: 48344 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 77 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44